THE RELATIONSHIP BETWEEN ANTENATAL CARE SERVICES AND WEIGHT IN NEWBORN BABIES AT THE BINEH KRUENG HEALTH CENTER WORKING AREA, TANGAN-TANGAN DISTRICT, SOUTHWEST ACEH REGENCY - Darwis, Aryandi; Fajriana, Eulisa; Gusweni, Mira; Naimah, Naimah (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Low BirthWeight (LBW) is a newborn whose birth weight is less than 2500 grams. LBW is one of the factors that causes mortality, morbidity, and disability in neonates and infants. Bineh Krueng Health Center in the period 2016 - 2017, recorded the occurrence of LBW cases, as many as 31 cases in 2016 and 5 cases up to March 2017. This research aims to determine the factors associated with the incidence of LBW at the Bineh Krueng Community Health Center, Tangan-tangan District. Method: This research uses a cross- sectional design. It was carried out from 03 to 11 July 2017. The research population was all 234 mothers who gave birth while the sample was 83 mothers who met the inclusion criteria. The sampling technique is random sampling (Snowball sampling). Data collection used questionnaires and observation of KIA books with checklist sheets. The data analysis used was univariate and bivariate analysis with the chi-square statistical test. Results: The research results showed LBW (41%) and good antenatal care service respondents (63.4%). The statistical test results showed that there was a relationship between antenatal care services (p-value=  0.0001). Recommendation: Puskesmas officers to work together with various related parties such as stakeholders, community leaders, and others when providing counseling and assistance to pregnant or already giving birth mothers to prevent the occurrence of LBW.